DIGITAL CAPITAL AS INFORMAL SOCIAL PROTECTION IN THE PANDEMIC COVID-19’S ERA (CASE STUDY OF THE WAYANG KULIT ASSOCIATION IN YOGYAKARTA) - Chindy Respa; Johanna Debora Imelda (UNIVERSITAS PAKUAN, 2021)
This article explains digital capital in the wayang kulit (Javanese traditional shadow puppet) association in Yogyakarta during the Covid-19 pandemic era and how its digital capital can protect and serve as informal social protection for the wayang kulit artists association in Yogyakarta in the difficult time. Following the case study method is to investigate WL (Ki SN) association, the group of wayang kulit GP (Ki CB) and SK (Ki GS). The three associations were chosen because they can survive in the middle of the pandemic by holding wayang kulit performances virtually using existing social capital and digital capital. Based on the research results show during the Covid-19 pandemic, digital capital is more effective in providing social protection for group or associations of wayang kulit in Yogyakarta than the traditional social capital scene. The higher the digital capital has seen from the virtual social network (subscriber and viewer or virtual audience), norms of reciprocity, and trust existing with external parties to increase the virtual shows, therefore it can meet the economic needs and welfare of every member in the group and association for facing the pandemic. This research offers a new alternative framework related to digital capital as a informal social protection form. Meanwhile, the practical result is as references for wayang kulit artists to survive in the uncertainty of pandemic and adapt to the challenges of technological digitalization. In addition, it can suggest for the government in formulating rules and an effective model of social protection policy for wayang kulit performances, shadow puppet artists, and in general other artist who rely on art performance as their livelihoods.